Investigations into the nature of the potato psyllid toxin - Abernathy, Rella L., author; Cranshaw, Whitney, advisor; Bjostad, Louis, advisor (Colorado State University. Libraries, 1991)
The potato or tomato psyllid, Paratrioza cockerelli (Sulc) (Homoptera: Psyllidae) is a pest of many solanaceous crops in the western U.S. and causes a disease in potatoes and tomatoes known as "psyllid yellows". The disease is caused by a phytotoxin produced by the potato psyllid that is systemic and causes many morphological changes in the host plant which can lead to crop loss. The effects of potato psyllid feeding on the yield of several varieties of potato, tomato and pepper were investigated. Tissue cultured potatoes were studied under greenhouse conditions by infesting the plants with potato psyllids. Dramatic yield losses occurred in four cultivars of potato studied. Varietal responses showed that early maturing cultivars had less damage, as measured by loss of tuber yield, than later cultivars. Another effect caused by potato psyllid feeding was premature sprouting of newly harvested tubers. In this case, early maturing cultivars had a greater proportion of tubers sprouting than later maturing cultivars. Tomatoes and peppers were studied under field conditions and infested by naturally occurring psyllid populations. Of eight varieties of tomatoes evaluated, all sustained a loss in yield when infested with potato psyllids. A range of damage and different levels of infestation occurred within the varieties. Peppers, on the other hand did not show typical symptoms observed in tomatoes and potatoes. Of four varieties studied, only one showed a slight decrease in yield from potato psyllid infestation. Two other pepper varieties showed a gain in yield from potato psyllid feeding, though only one variety had a statistically significant increase in yield.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Paratrioza cockerelli; Potatoes -- Diseases and pests